ALK inhibitor-induced bradycardia: A systematic-review and meta-analysis. (November 2021) - Cirne, Filipe; Zhou, Shijie; Kappel, Coralea; El-Kadi, Adam; Barron, Carly C.; Ellis, Peter M.; Sanger, Stephanie; Leong, Darryl P.
Highlights: The CV adverse effects of ALK inhibitors were not widely appreciated initially. Bradycardia is being increasingly recognized as an adverse effect of these drugs. Although usually mild, the rate of ALK inhibitor-induced bradycardia is up to 9%. Crizotinib led to a higher risk of bradycardia compared to standard chemotherapy. Newer ALK inhibitors appear to have a similar risk of bradycardia as crizotinib. Abstract: Introduction: Anaplastic Lymphoma Kinase (ALK) inhibitors have revolutionized the treatment of advanced ALK-positive non-small cell lung cancer (NSCLC), improving progression-free survival. Bradycardia is a potential adverse effect of these agents. We aimed to determine the risk of bradycardia associated with ALK inhibitors in patients with advanced NSCLC. Materials and methods: We conducted a systematic search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, National clinical trial registry, and Web of Science Core Collection. We included all randomized controlled trials in which an ALK-inhibitor was compared with another ALK-inhibitor or standard chemotherapy. Meta-analyses were conducted to evaluate the pooled incidence rates of bradycardia and dizziness using fixed effect models. Results: The pooled incidence of bradycardia among 1737 individuals prescribed ALK inhibitors was 8% during a mean follow-up of 1.26 years. Crizotinib led to more bradycardia than standard chemotherapy (relative risk, RR 24.68, 95% CI 7.11–85.), while no difference was seen between crizotinib and alectinib (RR 1.12, 95% CI 0.79–1.59). The next-generation ALK inhibitors alectinib, brigatinib and lorlatinib combined resulted in a similar rate of bradycardia when compared to crizotinib (RR 0.77, 95% CI 0.57–1.04). All ALK inhibitors (as an aggregate) caused more dizziness (as a potential symptom of bradycardia) than standard chemotherapy (RR 1.88, 95% CI 1.44–2.44). Conclusion: Crizotinib for the treatment of NSCLC is associated with a higher risk for bradycardia compared to standard chemotherapy. There is no evidence of a difference in bradycardia risk between crizotinib and newer ALK inhibitors.